MEASUREMENT OF THE B(0)-(B)OVER-BAR(0) MIXING PARAMETER AND THE Z-]B(B)OVER-BAR FORWARD-BACKWARD ASYMMETRY - Acciarri, M; Adam, A; Adriani, O; Aguilarbenitez, M; Ahlen, S; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; et al. (1994)
We have measured the time integrated B0B0 mixing parameter and the forward-backward asymmetry in the process e+e- → bb using hadronic events containing muons or electrons. The data sample corresponds to 1,044,000 hadronic decays of the Z. From a fit to the momentum and transverse momentum distributions for single lepton and dilepton events, we have determined the B0B0 mixing parameter to be χB = 0.123 ± 0.012 (stat.) ± 0.008 (sys.), and the bb forward-backward asymmetry at the effective center-of-mass energy √s = 91.30 GeV to be Abb = 0.087 ± 0.011 (stat.) ± 0.004 (sys.) This measurement corresponds to a value of the effective electroweak mixing angle of sin2θw = 0.2335 ± 0.0021. © 1994.